Relationship Between Physicochemical Properties and Herbicidal Activity of 1,2,5-Oxadiazole N-Oxide Derivatives - Fernandez, Luciana Andrea (2005)
The relationship between the herbicidal activity of a number of novel 1,2,5-oxadiazole N-oxides and some physicochemical properties potentially related with this bioactivity, such as polarity, molecular volume, proton acceptor ability, lipophilicity, and reduction potential were studied. The semiempirical molecular orbital method AM1 was used to calculate theoretical descriptors such as dipolar moment, molecular volume, Mulliken´s charge and the octanol/water partition coefficients (log Po/w). The values of the reduction potentials (Er) were obtained by cyclic voltammetry. In addition, the retention factors (log k’w) on a reversed-phase high-performance liquid chromatography (RP-HPLC) column in pure aqueous mobile phases were measured for several N-oxide derivatives. The log k’w values show good correlation with the calculated values of log Po/w, showing that the chromatographic parameter can be used as lipophilicity descriptor for these compounds. The multiple regression analysis between the descriptors for the N-oxide derivatives and the herbicide activity indicate that the variance in the biological activity can be explained by changes in the lipophilicity and in the reduction potential.